2022
DOI: 10.1002/aepp.13275
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and time use in elderly vs. non‐elderly: An exploratory analysis

Abstract: In the US, elderly households are more food secure than younger households. A possible explanation is that increased time availability enables elderly households to adopt strategies to improve their food security. Using time use data, we find elderly households spend more time in meal preparation and eating time than younger households. Creating a matched dataset of household time use and food security, we find that meal preparation and eating time have a small contribution to differences in food insecurity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Berning et al (2023) take these ideas to examine whether this substitution of time in food preparation results in improved food security among older households relative to younger households. To do so they use the CPS Food Security Supplement linked to the American Time Use Survey (ATUS) from 2003 to 2018.…”
Section: Risk Factors For Food Insecurity Among Senior Householdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Berning et al (2023) take these ideas to examine whether this substitution of time in food preparation results in improved food security among older households relative to younger households. To do so they use the CPS Food Security Supplement linked to the American Time Use Survey (ATUS) from 2003 to 2018.…”
Section: Risk Factors For Food Insecurity Among Senior Householdsmentioning
confidence: 99%
“…Much of the literature found that seniors cut back on spending on food upon retirement, and thus claimed that consumption fell, whereas Hurst and Aguiar showed that seniors invested more time in the production of food so that the combined value of money and time left total food consumption unchanged at retirement. Berning et al (2023) take these ideas to examine whether this substitution of time in food preparation results in improved food security among older households relative to younger households. To do so they use the CPS Food Security Supplement linked to the American Time Use Survey (ATUS) from 2003 to 2018.…”
Section: Risk Factors For Food Insecurity Among Senior Householdsmentioning
confidence: 99%
“…High Ed are households with one household head that has a bachelor's degree or higher. households to report greater food security (Berning et al, 2022), the transition to lower levels of FI is much more marked for White than Black households.…”
Section: Resultsmentioning
confidence: 98%
“…We include the vector of age cohort indicators (AC) to control for differences in FI between households at different points in their lives. Recent work by Berning et al (2022) shows that FI incidence for all households follows a nonlinear path across ages, reaching its lowest levels after 80. We also include year and state indicator variables to control for space‐ and time‐invariant factors that can be related to FI probability.…”
Section: Empirical Methodsmentioning
confidence: 99%
See 1 more Smart Citation